ELSE: an ontology-based system integrating semantic search and e-learning technologies. Issue 5 (4th July 2017) - Barbagallo, A.; Formica, A.
ABSTRACT: ELSE (E-Learning for the Semantic ECM) is an ontology-based system which integrates semantic search methodologies and e-learning technologies. It has been developed within a project of the CME (Continuing Medical Education) program – ECM (Educazione Continua nella Medicina) for Italian participants. ELSE allows the creation of e-learning courses which are customized according to the needs and learning preferences of the user. It relies on a reference domain ontology and teaching multimedial interactive modules, referred to as Reusable Learning Objects (RLOs), which are annotated according to the concepts of the ontology. The SemSim semantic search method allows the selection of the set of RLOs that satisfy the user request at best in efficient way. This set is successively reorganized according to the learning preferences of the user. ELSE has been validated and experimented in the domain of osteoporosis, and the overall judgment about it is very positive, both in terms of usability and effectiveness of customization.